Exploring Items for Measuring Social Media Construct: An Exploratory Factor Analysis - Nasidi, Qaribu Yahaya; Ahmad, Muhamad Fazil; Dahiru, Jamila Mohammed (Journal of Intelligent Communication, 2022)
Exploratory factor analysis (EFA) is a technique for determining a measure’s factor structure and assessing its internal consistency or reliability. EFA is essential for determining which components should be included in the study instrument. Social media is one of the most critical factors that affect online shopping behaviour. Thus, this study aims to use exploratory factor analysis to validate an instrument measuring social media in the context of online shopping. The questionnaire used in this study is adapted from previous studies. The researchers utilised a cross-sectional research design to conduct the EFA, collecting data from 100 respondents using a structured survey. The result shows that the construct has one component. The KMO is 0.892, and the outcome of Bartlett’s Test of Sphericity was significant (Chisquare = 510.816, p-value 0.000; this indicated that the data are okay to proceed. Cronbach’s Alpha was higher than 0.7, meaning that all items are reliable. The study concludes that the instruments used to measure social media in this research are valid and reliable.